Review of community forestry monitoring systems in Nepal (Journal of Forest and Livelihood, 2024)
A study was conducted to review the monitoring systems of various stakeholders involved in local level forest management in Nepal. The purpose of this review is to assess the current status of monitoring, identify and document lessons learnt, and explore gaps and opportunities for possible interventions.The study looked mainly at two aspects of existing monitoring systems and practices: a) self-monitoring practices of FUGs), and b) collaborative monitoring practices between FUGs and four different categories of stakeholders - Government, donor field projects, I/NGOs and civil society. A review of concepts related to participatory monitoring is made based on the literature, and aconceptual framework has been proposed for the review of monitoring practices in the context of community forestry in Nepal. Key elements used in the analysis include a) meanings and perceptions of monitoring, b) purpose, c) focus and scale, d) approach, processes and tools, e)contributions to adaptive management.